Analisa Kepuasan Pengguna Aplikasi SKP (Sasaran Kerja Pegawai) Online Menggunakan Metode Servqual - Chandy Ophelia S (Jurnal Sistem Informasi Kaputama (JSIK), 2023)
SKP (Employee Performance Targets) online is a website-based application used by the Tebo Regency Government. This application was made to measure the Work Performance (Performance) of Civil Servants in the Tebo Regency Government environment, especially the Education and Culture Office. This application was made in 2019, the purpose of this study was to find out the extent to which government employees use the SKP Online application in terms of satisfaction in using the application. In this study the authors used the Servqual (Service Quality) method. By using 5 variables, namely tangibles, reliability, responsiveness, assurance, empathy for user perceptions. In this study, 25 ASN respondents were actively using the application. Data processing in this study uses smartPLS 3.0 software. The results of this study indicate that 4 variables, namely tangibles, responsiveness, empathy, and assurance have a significant effect on user perceptions, and 1 variable, namely Reliability, which has no significant effect on user perceptions.